Does Smoking Fool You? The Smoking Habits Influence on the Cognitive Abilities of Indonesians - Marsuki, Rahim (Faculty of Economics and Business, Hasanuddin University, 2023)
This study aims to analyze the influence of smoking habits on adolescents' cognitive abilities. The data used in this research is cross-section data from the Indonesia Family Life Survey batch 5 2014. The high rate of cigarette consumption for the age range 15 years and over in Indonesia has become a very serious concern. The smoking habit has many negative impacts on human brain development which in the long term will affect the quality of human resources in Indonesia. by exploring IFLS 2014 data, we found 6,908 teenage respondents who smoke. This figure is quite large, reaching 8% of all respondents. This research uses logistic regression analysis to see the impact of the independent variable on the dependent variable. The research results show that together smoking habits, education, history of hypertension, sleep quality and age have a significant effect on a person's cognitive abilities. Partially, smoking habits, history of hypertension, and age have a significant negative effect on a person's cognitive abilities. Meanwhile, education and sleep quality have a significant positive effect on a person's cognitive abilities. Gender partially has no effect on cognitive abilities.